TOOL FOR RESEARCHING THE DYNAMIC SYSTEM OF METAL-CUTTING MACHINE (World Science, 2018)
Dynamic characteristics of the system flexibility of the machine affect the accuracy of machining, so the study of this problem is very important. Fluctuations of the machine elements significantly affect the error of the shape of the workpiece. The quality of the processing is determined not so much by the static displacements between the tool and the workpiece but the stability of the machine system as a whole. There are many solutions of vibroacoustic diagnostics devices for machines and machine-tools in the related publications. Defects in the spectrum of vibroacustic signals are found in the process of manufacturing and assembling machines in the form of discrete components, parameters of which are used in vibroacoustic diagnostics as informative diagnostic features. Along with that there is, but not so common, another type of dynamic system analysis of the machine, which can be carried out by experimental methods, or, in particular, by simulating the perturbation of a dynamic system by cutting forces of special type. Imitated disturbance is carried out by using a tool of a special form. During the processing cutting edges of the tool create a pseudorandom process with certain statistical characteristics, in particular, the correlation function. The proposed design of the tool makes it possible to perform the research of frequency parameters of the dynamic system of the machine without complex loading devices.